Respuesta :
The general equation of a circle is: [tex](x-a)^2+(y-b)^2=r^2[/tex], where [tex](a,b)[/tex] is the center of the circle and [tex]r[/tex] is its radius. We'll put the equation of the statement in the general form:
[tex]x^2+6x+y^2-4y=23\\\\ x^2+6x+\underline{9}+y^2-4y+\underline{4}=23+\underline{9}+\underline{4}\\\\ (x+3)^2+(y-2)^2=36\\\\ (x+3)^2+(y-2)^2=6^2[/tex]
Then, by comparing the general equation of the circle and the equation above, we have:
[tex]\boxed{\text{Center:}~(-3,2)}\\\\ \boxed{\text{Radius:}~r=6~u.c.}[/tex]
[tex]x^2+6x+y^2-4y=23\\\\ x^2+6x+\underline{9}+y^2-4y+\underline{4}=23+\underline{9}+\underline{4}\\\\ (x+3)^2+(y-2)^2=36\\\\ (x+3)^2+(y-2)^2=6^2[/tex]
Then, by comparing the general equation of the circle and the equation above, we have:
[tex]\boxed{\text{Center:}~(-3,2)}\\\\ \boxed{\text{Radius:}~r=6~u.c.}[/tex]
Answer:
The coordinates (x,y) are -3,2 while the radius is 6cm
Step-by-step explanation:
The general form of the equation of a circle may be given as
(x - a)² + (y - b)² = c²
where c is the radius, a and b are the coordinates of the center of the circle along the x and y axis.
Given the circle
x^2 + 6x + y^2 - 4y =23
To make it similar to the general form
x^2 + 6x +9 + y^2 -4y + 4 =23 + 9 + 4
Factorizing
(x + 3)² + (y - 2)² = 36
Comparing with the general form,
c² = 36
c = √36
= 6 cm ( this is the radius)
a = -3, b = 2